PREVENTING CORRUPTION RISKS IN PUBLIC ADMINISTRATION: FACTORS, STRATEGIES, AND SYSTEMATIC APPROACHES (TSUL LEGAL REPORT, 2026)
The prevention of corruption risks in public administration has become a pressing issue with dire consequences at both the national and global levels, necessitating legislative and practical measures in the fast-paced world. This paper highlights various risk factors, including individual, operational, external, internal, and systemic elements, which contribute to corruption within public institutions. More importantly, the article emphasizes the need to distinguish and clearly identify these risk factors for more effective governance while also exploring the theoretical and practical implications of corruption risk assessment. The study recommends a systematic approach for evaluating and managing corruption risks, involving stages such as risk identification, analysis, and mitigation. Additionally, the paper presents a range of strategies, such as enhancing the code of conduct for state officials, improving transparency in public procurement, and reinforcing budgetary accountability. By effectively managing these risks with sufficient resolve, public trust in government institutions can be strengthened, ensuring better governance and the targeted use of public resources.